Depression, suicidal ideation and quality of life of community health workers - Alves, Verônica de Medeiros (2021)
Community Health Agents are part of the Family Health Strategy and have duties that must be followed in health services. There is a need to recognize the work of the community health worker and value their working conditions, as well as to pay attention to behaviors that may compromise their quality of life and the development of mental disorders such as depression and suicidal behavior. This study aims to identify signs and symptoms of depression and suicidal ideation and to assess the quality of life of community health workers. This is a cross-sectional epidemiological research, with a quantitative approach of a descriptive character. An identification questionnaire, Depression scale (CES-D) and the WHOQOL-BREF quality of life questionnaire were used. The research site was in 14 Basic Health Units in the Municipality of Arapiraca-AL, with a sample of 114 Community Health Agents. The data were analyzed using the SSPS program, version 20. Among the research participants, 34 (26 , 8%) were at risk for depression, 5 (3.9%) claimed to think of a way to commit suicide and 4 (3.1%) attempted suicide in the last month. Depression correlated with quality of life identified a higher mean (60.2 ± 14.9) in the domain of social relationships and a lower mean (40.1 ± 16.9) in the physical domain in the group at risk for depression. This study shows that quality of life should not be studied in a fragmented way, and it is necessary to associate it with other issues with depression and suicidal ideation.